PENERAPAN KOMPETENSI MANAJERIAL KEPALA SEKOLAH DALAM PELAKSANAAN PROGRAM SEKOLAH ADIWIYATA UPT SPF SD INPRES PA'BAENG-BAENG 1 DI MAKASSAR - Rubianti . (STKIP Pembangunan Indonesia Makassar, 2022)
This study aims to find out: (1) How is the managerial competence of the principal of UPT SPF SD Inpres Pa'baeng-Baeng 1; (2) How is the upt SPF adiwiyata school program SD Inpres Pa'baeng-Baeng 1; and (3) how to apply the managerial competence of the principal in the implementation of the UPT SPF adiwiyata school program at SD Inpres Pa'baeng-Baeng 1 This research is qualitative research conducted using a descriptive approach. The subjects of this study were principals and teachers at UPT SPF SD Inpres Pa'baeng-Baeng 1. Data collection techniques use interviews, observations, and documentation. Data analysis techniques include data reduction, data presentation and conclusion drawing/verification The results of the research (1) The managerial competence of the principal at SD Inpres Pa'baeng-baeng 1 is quite good, especially in preparing activity planning, empowering teachers and staff well, being able to manage facilities and infrastructure, establishing good relations with the community environment, managing finances in an accountable, transparent manner and carrying out monitoring and evaluation activities on teaching and learning activities; (2) The adiwiyata school program carried out by integrating the curriculum and the support and participation of teachers, staff and students in this activity is good. But the availability of means is still lacking; (3) The application of the managerial competence of the principal in the implementation of the adiwiyata school program at SD Inpres Pa'baeng-Baeng 1 is quite good, especially in preparing the adiwiyata school program planning, managing teachers and staff to be involved and supporting the adiwiyata school program has been done well, developing a curriculum by integrating in the adiwiyata program in learning and the managerial competence of the principal in monitoring and evaluating the implementation of the adiwiyata school program the adiwiyata school program has been well done. Keywords: Managerial Competence, Principal, Adiwiyata Program